تطبيق آليات السياسة النقدية للحد من آثار الصدمة النفطية على الاقتصاد الجزائري دراسة تحليلية لوضعية المؤشرات الكلية للاقتصاد الجزائري خلال الفترة 2011-2021 - لجدل, خالد (جامعة الوادي - University of Eloued, 2023)
تعاني غالبية الاقتصاديات النفطية في العالم من تدهور أسعار المواد النفطية في أسواقها الدولية، خصوصا وإذا كانت تلك الاقتصاديات تعتمد وبشكل كبير على تلك المواد في تحصيل مواردها المالية وإثراء صناديق الصرف والنقد لديها من أجل بناء ميزانيتها العامة وتمويل مشاريها الاستثمارية الكلية. ويعتبر الاقتصاد الجزائري بغير بعيد عن تلك الاقتصاديات، من حيث تركيبة مصادر موارده المالية، إذ يتسم بصفة اقتصاد الريع النفطي، الذي يمثل المكون الرئيس والأساسي الذي تبني عليه الجزائر آمالها الاقتصادية والمالية والاجتماعية وحتى السياسية. وكغيرها من دول العالم الريعي، فإن الجزائر تسعى وفي كل مرة إلى إيجاد حلول اقتصادية من خلال تطبيق مختلف آليات سياستها النقدية، بغية الوصول إلى حلول ولو بسيطة تؤدي حتما إلى مجابهة الاختلالات الاقتصادية التي أنتجها تدهور أسعار المواد النفطية في أسواقها العالمية، والتي أثرت وبشكل صارخ على العديد من المؤشرات الكلية لاقتصادها. The majority of the oil economies in the world suffer from the deterioration of the prices of petroleum products in their international markets, especially if these economies rely heavily on these materials in collecting their financial resources and enriching their exchange and monetary funds in order to build their general budget and finance their overall investment projects. The Algerian economy is not far from those economies, in terms of the composition of its financial resources, as it is characterized by the oil rent economy, which represents the main and basic component in which Algeria builds its economic, financial, social and even political hopes. Like other rentier states in the world, Algeria seeks, every time, to find economic solutions through the application of the various mechanisms of its monetary policy, which have blatantly affected on many macro indicators of its economy.
The Applying monetary policy mechanisms to reduce the effects of the oil shock on the Algerian economy - An analytical study of the state of the Algerian economy during the period 2011-202
مقال
Keywords: أسعار النفط ; السياسة النقدية ; النمو الاقتصادي ; ميزان المدفوعات ; احتياطي الصرف; ds: Oil prices, Monetary policy, Economic growth, Balance of payments, Exchange reserve